2021
DOI: 10.1002/ajh.26181
|View full text |Cite
|
Sign up to set email alerts
|

Ineffectiveness of high‐dose methotrexate for prevention of CNS relapse in diffuse large B‐cell lymphoma

Abstract: Central nervous system (CNS) relapse affects 5% of diffuse large B‐cell lymphoma (DLBCL) patients and portends a poor prognosis. Prophylactic intravenous high‐dose methotrexate (HD‐MTX) is frequently employed to reduce this risk, but there is limited evidence supporting this practice. We conducted a multicenter retrospective study to determine the CNS relapse risk with HD‐MTX in DLBCL patients aged 18–70 years treated in Alberta, Canada between 2012 and 2019. Provincial guidelines recommended HD‐MTX for patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 29 publications
(96 reference statements)
4
53
0
Order By: Relevance
“…Recent observational studies have attempted to improve on previous studies which tended to be limited by small sample sizes and confounding factors. One of the largest analyses to date with 326 patients at high risk of CNS relapse did not find HDMTX effective, but most of the CNS relapses were concomitant CNSsystemic relapses (59% of cases) rather than isolated CNS relapses [9]. The authors found that optimizing systemic disease control with autologous transplant or intensive chemoimmunotherapy led to a significantly lower rate of CNS relapse, adding support to the hypothesis that improved systemic control of the disease is perhaps more important to reduce concurrent CNS-systemic relapse than HDMTX.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent observational studies have attempted to improve on previous studies which tended to be limited by small sample sizes and confounding factors. One of the largest analyses to date with 326 patients at high risk of CNS relapse did not find HDMTX effective, but most of the CNS relapses were concomitant CNSsystemic relapses (59% of cases) rather than isolated CNS relapses [9]. The authors found that optimizing systemic disease control with autologous transplant or intensive chemoimmunotherapy led to a significantly lower rate of CNS relapse, adding support to the hypothesis that improved systemic control of the disease is perhaps more important to reduce concurrent CNS-systemic relapse than HDMTX.…”
Section: Discussionmentioning
confidence: 99%
“…With concerns around the effectiveness of intrathecal (IT) prophylaxis which may not reach measurable concentrations in the brain parenchyma [2,3], systemic high-dose methotrexate (HDMTX) has been recommended by some guidelines for patients at high risk of CNS relapse [4,5]. However, evidence supporting this practice is limited to small retrospective studies [6,7], and recent studies demonstrate no benefit of HDMTX in preventing CNS relapse [8,9]. Given the potential for HDMTX to be associated with significant toxicity and delays of RCHOP chemotherapy which may compromise systemic control [10], further evaluation of the role of HDMTX in mitigating the risk of CNS recurrence is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…[28,29] However, there are also reports which show little benefit from HD-Mtx as a single agent, [30,31] but from its part of intensive regimens such as R-CODOX-M/R-IVAC and R-Hyper-CVAD/R-MA. [32] We believe that HD-Mtx and HD-cytarabine together might be very The improving outcome in our patients encourages us to continue to explore R-Hyper-CVAD/R-MA for high-risk patients in a prospective clinical trial. This is a highly toxic regimen, during which febrile neutropaenias are expected and not a cause for discontinuation.…”
Section: Outcome After Lymphoma Progressionmentioning
confidence: 84%
“…Systemic high-dose methotrexate produces more equal concentrations in the subarachnoid space and has been shown to be effective in high-risk patients [ 28 ]. However, a recent study failed to show a benefit in high-risk patients (defined as high-risk CNS-IPI and double hit) [ 29 ], and there is still a debate regarding the optimal schedule and dose to be used [ 9 ].…”
Section: Discussionmentioning
confidence: 99%